Dysregulation of sphingolipid metabolism in pain - Wang, Jianfeng; Zheng, Guangda; Wang, Linfeng; Meng, Linghan; Ren, Juanxia; Shang, Lu; Li, Dongtao; Bao, Yanju (Frontiers in Pharmacology, 2024)
Pain is a clinical condition that is currently of great concern and is often caused by tissue or nerve damage or occurs as a concomitant symptom of a variety of diseases such as cancer. Severe pain seriously affects the functional status of the body. However, existing pain management programs are not fully satisfactory. Therefore, there is a need to delve deeper into the pathological mechanisms underlying pain generation and to find new targets for drug therapy. Sphingolipids (SLs), as a major component of the bilayer structure of eukaryotic cell membranes, also have powerful signal transduction functions. Sphingolipids are abundant, and their intracellular metabolism constitutes a huge network. Sphingolipids and their various metabolites play significant roles in cell proliferation, differentiation, apoptosis, etc., and have powerful biological activities. The molecules related to sphingolipid metabolism, mainly the core molecule ceramide and the downstream metabolism molecule sphingosine-1-phosphate (S1P), are involved in the specific mechanisms of neurological disorders as well as the onset and progression of various types of pain, and are closely related to a variety of pain-related diseases. Therefore, sphingolipid metabolism can be the focus of research on pain regulation and provide new drug targets and ideas for pain.